Escritores argentinos en la prensa. Roberto Arlt y Enrique González Tuñón "al margen" de la noticia (1937-1942) - Juárez, Laura Susana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2008)
The article is focused on some journalistic chronicles by Roberto Arlt and Enrique González Tuñón, issued by the late 1930s and the beginning of the 1940s, in a massive newspaper like El Mundo. These chronicles deal with the same subject matter (the World War II, current events and curiosities) and are written by using similar procedures like "Glosa" of the news, and fictional expansión of the international newswires. Therefore, our intent is to reflect about this cross between fiction and chronicle in a time in which both writers had gain a highly respected position within the literature as well as the journalism